Preparation method of amorphous and crystal WO3 double-layer electrochromic film
Through radio frequency magnetron sputtering method and annealing treatment technology, WO3 double-layer electrochromic film was prepared, which solved the problems of long response time and low cycle stability, and achieved rapid response and high stability electrochromic performance, suitable for large Large-scale production.
Patent Information
- Application Number
- CN202411375255.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
The existing WO3 electrochromic films have problems with long response time and low cycle stability. The use of hydrothermal and electrodeposition methods during the preparation process is not conducive to large-scale and large-scale production.
The amorphous WO3 film was prepared at room temperature by radio frequency magnetron sputtering, and annealed at air atmosphere of 350°C to 450°C to form a crystalline WO3 film. Then, the upper amorphous WO3 film was prepared again at room temperature to form a Double-layer structure.
The rapid response time and high cycle stability of the double-layer electrochromic film are achieved, suitable for large-scale production, combined with the large transmittance modulation amplitude of amorphous WO3 and the stability of crystal WO3, showing excellent electrogenesis Color distortion comprehensive performance.
Smart Images

Figure CN119191722A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oxide thin films, and in particular relates to a method for preparing an amorphous and crystalline WO3 double-layer electrochromic thin film. Background Art
[0002] Electrochromic smart glass has the advantages of a large optical adjustment range, simple and diverse preparation process, active adjustment, and little influence from environmental factors, making it the most likely potential material for smart windows for commercial application. After exploring the electrochromic phenomenon in transition metal oxides (TMOs) in the mid-1960s, WO3 became one of the most attractive electrochromic materials due to its large optical contrast, good cycle stability, gentle color change and easy synthesis. According to previous studies, the electrochromic performance of WO3 depends largely on its crystal structure. Amorphous tungsten oxide (a-WO3) films have fast coloring or bleaching response and high coloring efficiency, which is due to the disordered arrangement of [WO6] octahedrons in the structure providing a large number of open polygonal voids for ion transport. However, due to the loose structure and low chemical stability, the electrochromic stability of a-WO3 films is poor. On the other hand, crystalline tungsten oxide (c-WO3) films show higher stability due to the long-range order of atoms in the crystal, denser structure, stronger interatomic bonding and lower electrolyte dissolution rate. However, c-WO3 thin films have low coloring efficiency and poor switching speed. Therefore, it is particularly important to develop WO3 electrochromic materials with both fast switching response and high cycle stability.
[0003] Some studies have synthesized WO3 nanowire array films with crystalline and amorphous core-shell structures by combining hydrothermal and electrodeposition. Other studies have prepared WO3 nanorod films with hexagonal phase / amorphous core-shell structures by two-step hydrothermal treatment and spin coating.
[0004] However, the above studies all used hydrothermal and electrodeposition methods in the preparation of thin films, which will be unfavorable for large-scale and large-area production. Summary of the invention
[0005] The invention provides a method for preparing an amorphous and crystalline WO3 double-layer electrochromic film, so as to solve the existing problems of long response time and low cycle stability of the film color change.
[0006] The technical solution adopted by the present invention comprises the following steps: (1) Take the cut conductive glass ITO and use acetone, anhydrous ethanol and deionized water to ultrasonically clean it in sequence, and use a nitrogen gun to blow away the residual moisture on the surface of the substrate; (2) Based on WO3 target, amorphous WO3 thin film a-WO3 with a thickness of 110nm-120nm was prepared at room temperature by radio frequency magnetron sputtering; (3) Annealing treatment is continued for 1.5h-2.5h at 350°C-450°C in air atmosphere to obtain a crystalline WO3 film c-WO3; (4) Based on the c-WO3 film, the a-WO3 film with a thickness of 140nm-155nm was prepared at room temperature using a magnetron sputtering method based on the WO3 target material to obtain a double-layer film with an upper layer of a-WO3 and a lower layer of c-WO3.
[0007] The size of the conductive glass ITO cut in step (1) of the present invention is 1.0 cm×2.0 cm, and the cleaning time is 10 min to 15 min.
[0008] The WO3 target material in step (2) of the present invention has a diameter of 50 mm, a thickness of 5 mm and a purity of 99.99%.
[0009] The magnetron sputtering conditions in step (2) of the present invention are: power of 90W-110W, ratio of argon to oxygen of 100:0-70:30, chamber pressure of 0.8Pa-2.0Pa at room temperature, and sputtering time of 10min-20min.
[0010] The magnetron sputtering conditions in step (2) of the present invention are: sputtering power of 100 W, argon to oxygen ratio of 90:10, chamber pressure maintained at 1.4 Pa at room temperature, and sputtering time of 15 min.
[0011] In step (3) of the present invention, the annealing treatment is carried out continuously for 2 hours at 400° C. in an air atmosphere.
[0012] The WO3 target material in step (4) of the present invention has a diameter of 50 mm, a thickness of 5 mm and a purity of 99.99%.
[0013] The magnetron sputtering conditions in step (4) of the present invention are: power of 90W-110W, ratio of argon to oxygen of 100:0-70:30, chamber pressure of 0.8Pa-2.0Pa at room temperature, and sputtering time of 25min-35min.
[0014] The magnetron sputtering conditions in step (4) of the present invention are: sputtering power of 100 W, argon to oxygen ratio of 90:10, chamber pressure maintained at 1.4 Pa at room temperature, and sputtering time of 30 min.
[0015] An amorphous and crystalline WO3 double-layer electrochromic film prepared by the method.
[0016] The advantages of the present invention are that the magnetron sputtering technology and annealing process with the advantages of fast deposition speed, high efficiency, close bonding with the substrate, and suitability for large-scale process production are adopted, so that the prepared double-layer electrochromic film has both the good cycle stability of crystalline WO3 and the large transmittance modulation amplitude and short color change response time of amorphous WO3. By preparing WO3 with amorphous and crystalline heterostructures, the comprehensive color change performance of WO3 can be improved. The upper amorphous structure layer is conducive to shortening the response time of the film color change, while the lower crystalline structure layer ensures the cycle stability of the film. The synergistic effect of the two makes the heterostructure WO3 have the advantages of both amorphous and crystalline WO3, thereby showing excellent electrochromic comprehensive performance. At the same time, the regulation mechanism of crystalline and amorphous WO3 materials in the electrochromic process is also studied. The present invention provides a certain reference value for the design and development of high-efficiency electrochromic films and devices thereof. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic diagram of the structure of WO3 electrochromic film; Figure 2 It is the XRD spectra of the embodiment and the comparative example; Figure 3 The SEM images of amorphous and crystalline states before cycling are shown in (a) Comparative Example 1, (b) Comparative Example 2, (c) Example 1, (d) Comparative Example 3, and (e) Comparative Example 4. Figure 4 The SEM images of amorphous and crystalline states after cycling, (a) Comparative Example 1, (b) Comparative Example 2, (c) Example 1, (d) Comparative Example 3, (e) Comparative Example 4; Figure 5 The cyclic voltammetry curves at different scanning speeds are shown in the figure; (a) Comparative Example 1, (b) Comparative Example 2, (c) Example 1, (d) Comparative Example 3, (e) Comparative Example 4; (f) the relationship between the cathode peak current and the square root of the scanning speed; Figure 6 The cyclic voltammetry curves of the thin film after 600 cycles at a scanning rate of 0.05 V / s; (a) Comparative Example 1, (b) Comparative Example 2, (c) Example 1, (d) Comparative Example 3, (e) Comparative Example 4; Figure 7 Graphs showing the transmittance of the film after applying different coloring voltages; (a) Comparative Example 1, (b) Comparative Example 2, (c) Example 1, (d) Comparative Example 3, and (e) Comparative Example 4; Figure 8 (a) Comparative Example 1; (b) Comparative Example 2; (c) Example 1; (d) Comparative Example 3; (e) Comparative Example 4, the transmittance of the film after 600 electrochemical cycles; Fig. 9The XPS spectra of W 4f (ac), Li 1s (df) and O 1s (gi) in the colored state of Comparative Example 1, Example 1 and Comparative Example 5; Fig.10 It is the XPS spectra of W 4f (ac), Li 1s (df) and O 1s (gi) in the faded state of Comparative Example 1, Example 1 and Comparative Example 5. DETAILED DESCRIPTION Example 1
[0018] The following steps are involved: (1) Take a 1.0 cm × 2.0 cm conductive glass (ITO) and ultrasonically clean it with acetone, anhydrous ethanol and deionized water for 10 min each. Use a nitrogen gun to blow away the residual water on the surface of the substrate. (2) Based on a WO3 target with a diameter of 50 mm, a thickness of 5 mm and a purity of 99.99%, a 115 nm thick amorphous WO3 film a-WO3 was prepared at room temperature by RF magnetron sputtering (QMS-450, Shenyang Weicom General Instrument Co., Ltd., China). The sputtering power was 100 W, the ratio of argon to oxygen was 90:10, the chamber pressure was maintained at 1.4 Pa at room temperature, and the sputtering time was 15 min. (3) Annealing treatment was carried out for 2 h at 400 °C in air atmosphere (tubular annealing furnace, OTF-1200X, Hefei Kejing Material Technology Co., Ltd., China) to obtain a crystalline WO3 film c-WO3; (4) Based on the c-WO3 film, a-WO3 film with a thickness of 148 nm was prepared at room temperature by magnetron sputtering based on a WO3 target with a diameter of 50 mm, a thickness of 5 mm and a purity of 99.99%. The sputtering power was 100 W, the ratio of argon to oxygen was 90:10, the chamber pressure was maintained at 1.4 Pa at room temperature, and the sputtering time was 30 min. A double-layer film with an upper layer of a-WO3 and a lower layer of c-WO3 was obtained. Example 2
[0019] The following steps are involved: (1) Take the cut 1.0 cm × 2.0 cm conductive glass ITO and ultrasonically clean it with acetone, anhydrous ethanol and deionized water for 12 min each. Use a nitrogen gun to blow away the residual moisture on the surface of the substrate. (2) Based on a WO3 target with a diameter of 50 mm, a thickness of 5 mm and a purity of 99.99%, a 110 nm thick amorphous WO3 film a-WO3 was prepared at room temperature using a radio frequency magnetron sputtering method (QMS-450, Shenyang Weicom General Instrument Co., Ltd., China). The sputtering power was 90 W, the ratio of argon to oxygen was 100:0, the chamber pressure was maintained at 0.8 Pa at room temperature, and the sputtering time was 10 min. (3) Annealing treatment was carried out for 1.5 h at 350 °C in air atmosphere (tubular annealing furnace, OTF-1200X, Hefei Kejing Material Technology Co., Ltd., China) to obtain a crystalline WO3 film c-WO3; (4) Based on the c-WO3 film, a-WO3 film with a thickness of 140 nm was prepared at room temperature using a magnetron sputtering method based on a WO3 target with a diameter of 50 mm, a thickness of 5 mm and a purity of 99.99%. The sputtering power was 90 W, the ratio of argon to oxygen was 100:0, the chamber pressure was maintained at 0.8 Pa at room temperature, and the sputtering time was 25 min. A double-layer film with an upper layer of a-WO3 and a lower layer of c-WO3 was obtained. Example 3
[0020] The following steps are involved: (1) Take the cut 1.0 cm × 2.0 cm conductive glass ITO and ultrasonically clean it with acetone, anhydrous ethanol and deionized water for 15 min each. Use a nitrogen gun to blow away the residual moisture on the surface of the substrate. 2. Based on a WO3 target with a diameter of 50 mm, a thickness of 5 mm and a purity of 99.99%, a 120 nm thick amorphous WO3 film a-WO3 was prepared at room temperature using a radio frequency magnetron sputtering method (QMS-450, Shenyang Weicom General Instrument Co., Ltd., China). The sputtering power was 110 W, the ratio of argon to oxygen was 70:30, the chamber pressure was maintained at 2.0 Pa at room temperature, and the sputtering time was 20 min. 3. Annealing treatment was carried out for 2.5 h at 450 ° C in air atmosphere (tubular annealing furnace, OTF-1200X, Hefei Kejing Material Technology Co., Ltd., China) to obtain a crystalline WO3 film c-WO3; 4. On the basis of c-WO3 film, based on WO3 target material with a diameter of 50 mm, a thickness of 5 mm and a purity of 99.99%, a-WO3 film with a thickness of 155 nm was prepared at room temperature by magnetron sputtering method. The sputtering power was 110 W, the ratio of argon to oxygen was 70:30, the pressure in the chamber was maintained at 2.0 Pa at room temperature, and the sputtering time was 35 min to obtain a double-layer film with an upper layer of a-WO3 and a lower layer of c-WO3.
[0021] The effects of the present invention are further described below in conjunction with a comparison of a specific comparative example and embodiment 1.
[0022] Example 1 The preparation method is the same as above.
[0023] Comparative Example 1 The difference between this comparative example and Example 1 is that only a c-WO3 film with a thickness of 115 nm is grown, and an amorphous WO3 film is not grown. The other steps and parameters are the same as those in the example.
[0024] Comparative Example 2 The difference between this comparative example and Example 1 is that on the basis of the bottom crystalline c-WO3 film with a thickness of 115nm, the magnetron sputtering method is continued to be used to prepare the upper a-WO3 film with a thickness of 73nm, the sputtering time is 10min, and the other steps and parameters are the same as those in the example.
[0025] Comparative Example 3 The difference between this comparative example and Example 1 is that on the basis of the bottom crystalline c-WO3 film with a thickness of 115nm, the magnetron sputtering method is continued to be used to prepare the upper a-WO3 film with a thickness of 322nm, the sputtering time is 50min, and the other steps and parameters are the same as those in the example.
[0026] Comparative Example 4 The difference between this comparative example and Example 1 is that no c-WO3 film is grown, only an a-WO3 film with a thickness of 262 nm is grown, the sputtering time is 30 min, and the other steps and parameters are the same as those in Example 1.
[0027] Table 1 Sputtering time and thickness of bottom layer and upper layer WO3 in Example 1 and Comparative Examples 1 to 4
[0028] 1. Structure and phase composition of WO3 thin film Depend on Figure 2 It can be observed from the XRD spectra of Example 1 and the comparative example that the WO3 film after annealing at 400°C clearly exhibits diffraction peaks at 2θ= 23.1°, 24.4° and 34.2°, corresponding to the (002), (200) and (202) planes, respectively, indicating that the crystallinity of the film has been improved after annealing, and it has a good match with the monoclinic WO3 [JCPDS 20-1324], indicating that a crystal structure has been formed. And as the sputtering time of the upper layer WO3 increases and the thickness of the a-WO3 covering increases, the crystallization peak intensity of the bottom layer WO3 gradually decreases, indicating that the increase in the thickness of the amorphous layer makes the surface more amorphous, showing amorphous characteristics.
[0029] (II) Film surface and cross-sectional morphology analysis Figure 3 The upper right corner of ad is the SEM image of the film cross section. It can be clearly observed that with the increase of the second magnetron sputtering time, the thickness of the upper amorphous structure a-WO3 gradually increases, which are 73 nm, 148 nm and 322 nm respectively, and the thickness of the bottom crystalline layer c-WO3 film is 115 nm. Figure 3 e The thickness of the amorphous layer grown for only 30 min is 262 nm. Observing the morphological changes on the film surface, as the amorphous WO3 film becomes thicker, the visible cracks on the film surface gradually decrease, and the film surface becomes smoother. When the sputtering time of the amorphous layer is 30 min and 50 min, almost no cracks are visible on the surface. This may be because the amorphous a-WO3 film is too thick to completely cover the crystal layer, showing amorphous characteristics, which is similar to the surface structure of growing only a single layer of amorphous WO3 film.
[0030] Comparing the SEM images before and after the cycle, Figure 3 Before the cycle Figure 4 The SEM image after cycling is compared Figure 3 a and Figure 4 a is the SEM characterization from 15 min to 0 min. There is almost no change before and after the cycle. The cracks on the film surface are still evenly distributed, the crack size increases slightly, and the cross section remains intact. Figure 3 b. Figure 3 c and Figure 4 b Figure 4 c, a thinner amorphous layer was grown for 10min and 30min respectively. After the cycle, there was no obvious crack on the surface of the film. From the cross section, it can be seen that the upper amorphous layer did not fall off. When the amorphous layer growth time was 30 min, there was no obvious crack on the surface of the film before and after the cycle. It can be seen that when the amorphous thickness is 148nm, it has good cycle stability. After multiple Li + The injection and withdrawal of ions have little effect on the film surface. However, when the growth time reaches 50 min, Figure 3 d and 4d, the film surface was seriously damaged after the cycle, and a large amount of surface peeling occurred. Figure 4 In the small area cross section of d, it can be seen that the upper amorphous layer almost completely disappears, leaving only the underlying crystalline structure. Figure 3e and 4e are amorphous WO3 films that only grow a single layer. They are also seriously damaged before and after the cycle. After the cycle, cracks larger than those of crystalline WO3 appear on the surface, and the surface is obviously different from the previous groups. After observing the cross section, it is found that the thickness becomes thinner, and even almost no obvious thickness can be seen. According to most papers, the WO3 film with amorphous non-crystalline structure has poor cycle stability, and the faster the ion injection and withdrawal, the higher the coloring efficiency, etc., while the WO3 film with a crystal structure has super strong cycle stability. In the present invention, as the thickness of the amorphous layer covers, the electrochromic performance of the film tends to be completely amorphous, which is reflected in the subsequent electrochemical performance and permeability.
[0031] (III) Analysis of electrochromic performance Cyclic voltammetry (CV) tests were performed at different scan rates between -1 V and +1 V. Figure 5 It can be seen that with the increase of the thickness of the amorphous layer, the area surrounded by the cyclic voltammetric characteristic curve gradually increases, which is positively correlated with the growth thickness of the amorphous layer. The larger the area of the cycle curve, the more ions are injected and withdrawn. It can be seen that when the amorphous layer is thicker, the more ions are injected and withdrawn. When the growth time of the amorphous layer is 30min, the CV curve of the bottom layer with crystal is Figure 5 e bottom layer without crystalline layer area is almost the same, it can be seen that when the amorphous growth time is 30min, ions may be mainly transmitted in the amorphous layer. As mentioned above, because the W atom is surrounded by six oxygen atoms in the amorphous state to form a WO6 octahedral structure, but because the combination of W elements and O elements in the disordered structure is more random, it cannot be completely guaranteed that each W element can be combined with 6 O elements, which will inevitably have some oxygen vacancies, resulting in different bond angles and bond lengths between WO bonds. The octahedral structure of WO6 is connected by O elements, which will produce four different ion transmission channels and storage channels. Three-dimensional disordered structures, namely triangular, quadrilateral, pentagonal and hexagonal channels, a large number of pentagonal and hexagonal ion channels are conducive to the transmission of Li ions, which makes the amorphous structure WO3 film have a larger ion capacity, faster coloring and fading speed, and a larger light modulation rate. However, after crystallization, the octahedral structure of WO3 only has quadrilateral channels and some oxygen vacancy channels, which will bring inconvenience to the transmission of Li ions, which will greatly reduce the injection and exit rate of Li ions.
[0032] The response speed of the film when circulating in the electrolyte depends on the diffusion coefficient of the ions. The ion diffusion coefficient D can be calculated from the cyclic voltammetry curves at different scanning speeds. According to the Randles-Sevcik law, the relationship is as follows:
[0033] Among them, Ip is the peak current (A), A is the working electrode area (cm 2 ), C0 is the electrolyte concentration (mol·mL -1 ), n is the number of electrons transferred during the reaction (1 or 3. Since the solution used in this example is LiClO4 / PC, n=1), v is the scan rate (V / s). The calculation results are as follows Figure 5 f, the slope of the fitting curve in the figure can intuitively show the size of the diffusion coefficient. The steeper the slope, the larger the diffusion coefficient. The calculated diffusion coefficients of different films are 0.0087×10 -10 cm 2 / s, 1.555×10 -10 cm 2 / s、4.013×10 -10 cm 2 / s, 13.23×10 -9 cm 2 / s and 4.290cm 2 / s, it can be clearly seen that the diffusion coefficients of 15min-30min and 0min-30min are almost the same. As the thickness of the amorphous layer increases, the slope of the curve also gradually increases. It can be seen that as the amorphous layer thickens, the diffusion of ions also increases. According to most paper reports, the amorphous WO3 film has a large ion diffusion coefficient, while the crystalline WO3 film has a small ion diffusion coefficient. From the analysis here, it can be seen that as the thickness of the amorphous layer continues to increase, the film gradually changes from the characteristics of the crystal to the characteristics of the amorphous, which will bring improvements in the optical and dynamic properties of the electrochromic film, but at the same time it will reduce the cycle stability performance. Therefore, considering the balance of these two aspects, it is found through experiments that when the thickness of the amorphous layer is about 148 nm, its cycle stability and transmittance are very good.
[0034] Compare the cyclic voltammetry curves with a scan rate of 0.05v / s before and after the cycle. Figure 6 ad, after 600 cycles, the area of the cycle curve has been reduced to a certain extent, Figure 7 The area of a is less reduced, which may be due to the fact that after cycling, part of the Li + The ions are embedded deeper into the crystal structure layer, which slows down the diffusion of ions and prevents them from completely exiting. Figure 7 The area of d that is reduced is relatively large. This is because after the cycle, the amorphous layer on the surface of the film falls off in a large area, resulting in a large reduction in the colorable amorphous layer. Figure 7The e area also decays a lot, which is also caused by the shedding of the amorphous layer film. This has been clearly seen in the previous SEM cross-sectional image. After the film falls off, the coloring sites are greatly reduced, and the ion storage area is greatly reduced. By comprehensively comparing the four different thicknesses of the amorphous layer, we found that the group with the least cycle decay is 15 min-30 min.
[0035] (IV) Optical performance analysis like Figure 7 ae is the transmittance of the film before the cycle after applying different coloring voltages. As the applied coloring voltage decreases, the transmittance of the film also decreases. And as the thickness of the amorphous layer increases, the transmittance of the film in the colored state also gradually decreases. Figure 7 The film after 600 cycles was tested by UV spectrophotometer at a wavelength of 630 nm. Due to the chronoamperometry used in the cycle test, the step pulse potential applied was ±1 V with a width of 20 s. Figure 7 The green curve in ae is the transmittance in the initial state, and the blue curve is the colored state. The transmittance in the colored state with -1 V applied is 2.97%, and its optical modulation range reaches 76.57%, which is almost consistent with the modulation rate of a single-layer amorphous WO3 film. It can be seen that when the thickness of the amorphous layer reaches 322 nm, the optical properties of the film almost completely show the characteristics of amorphous.
[0036] The voltage is -1V for 20s. The red curve is the faded state. The voltage is +1V for 20s. Finally, a constant potential of +1V is applied to the film for 15 min to ensure that the film fades completely.
[29] , test whether it is damaged, which is represented by the blue curve in the figure. Figure 8 We can see that the transmittance of the film after cycling cannot completely coincide with that of the initial state. Fig. 9 For films with amorphous layers in AD with a sputtering time less than 30 min (thickness less than 148 nm), the transmittance difference before and after the cycle is not large, close to the transparent state, but Fig. 9 d The transmittance of the film with amorphous layer sputtering time of 50 min (thickness 322 nm) is higher than that of the initial state. This is due to the shedding of the amorphous layer film, which has been fully explained in the previous analysis. The modulation range at the wavelength of 630 nm is observed, where Figure 8 The film with c of 15 min-30 min still maintained a high modulation range, which decreased from 62.71% before the cycle to 45.02%, and changed by 17.69% after the cycle. Figure 8 e Only a single layer of amorphous WO3 film is grown. It can be seen that the cycle stability of amorphous WO3 is the worst. After applying a continuous fading voltage, Li+ The most serious decline is in 15min-50min, from 76.57% before the cycle to 13.16%, with a large attenuation change of 63.41%. This may be due to the fact that the amorphous layer WO3 is too thick and a large amount of Li is embedded in it. + ions, and after the cycle, the fading voltage was continuously applied for 15 minutes, and the transmittance of the film exceeded the initial state, which may be related to the shedding of the surface amorphous layer. In summary, when the thickness of the amorphous layer is about 148 nm, the film has the best cycle stability and optical modulation range.
[0037] 5. X-ray photoelectron spectroscopy analysis Compare the X-ray photoelectron spectroscopy (XPS) spectra in the colored and faded states, such as Fig. 9 is the W 4f, Li 1s and O 1s spectra in the colored state, Fig. 9 (ac) It can be seen that the chemical valence of W element changes in the colored state after applying -1V voltage. Both the single-layer crystalline and non-static WO3 films contain a large amount of +5-valent W, making its color appear blue, while the content of +5-valent W in the film covered with amorphous layer is relatively small, which may be due to the large resistivity caused by the double-layer structure, thus making Li + The injection volume is small, due to Fig. 9 The XPS analysis of Li element in (df) can more intuitively show that Li + More Li+ was injected into the single-layer crystalline and amorphous states, while the amount injected into the double-layer structure covered by amorphous was significantly reduced, which may be conducive to the fading of the film. Combined with the above spectrophotometer analysis, although a large amount of Li+ was injected into the crystalline film to reduce W from +6 valence to +5 valence, its transmittance performance was not as good as that of the single-layer amorphous state, which may be related to Li + The coloring sites in the WO3 film make some Li+ enter the WO3 film, but they do not contribute to the discoloration of the film. It can be seen that the optical properties of the film cannot simply depend on Li+. + The amount of ion implantation and W 5+ This is consistent with the phenomenon reported by Wen mentioned above. In contrast, the Li + Ion implantation is more, W 5+ The content of Li+ is also high, and the transmittance is also low. It can be seen that Li+ injected into the amorphous WO3 film is more likely to show color change performance. This is why the WO3 film covered with an amorphous layer has a small amount of Li + Ion and W 5+ The reason why it can still show good optical performance under the condition of Fig. 9(gi) Regarding the O 1s spectrum, we can make a preliminary analysis of why Li + Ion and W 5+ The content is high, but the optical properties are average. Fig. 9 As can be seen in g, a large amount of Li + After injection, the oxygen vacancy intensity in the film is significantly enhanced. Fig. 9 i + After implantation, the oxygen vacancy intensity did not change significantly, which may be due to the Li + After being injected into the film, it reacts with the W element, and only a small part of it is in the oxygen vacancies. The situation of ion injection in the crystalline WO3 film is just the opposite. A large amount of Li + After being injected into the film, it is located in the oxygen vacancies and rarely reacts with W, resulting in an unsatisfactory color change effect.
[0038] like Fig.10 The W 4f, Li 1s and O 1s spectra in the faded state are shown in Figure 2. Fig.10 (ac) It can be seen that the chemical valence of W element changes in the colored state after applying +1V voltage. It can be seen that even after applying the fading voltage, the crystalline WO3 film still contains some W. 5+ , this part W 5+ It appears in a colored state, and the W in the double-layer structure and single-layer amorphous structure WO3 film covered with an amorphous layer 5+ The content is extremely low. Fig.10 (df) The XPS spectrum of Li can more intuitively observe the residual Li+. It can be seen that after covering the amorphous layer, the Li + The residual is greatly reduced, and the ion embedding in the film is not a linear accumulation process. As the cycle proceeds, the embedding of particles in the film may gradually slow down and tend to saturation, which will be beneficial to the stability of the optical properties of the film after cycling. Finally, combined with the O1s spectrum, it can be clearly observed that the oxygen vacancy content in the crystalline state is very large, but after fading, this part of the oxygen vacancy content is greatly reduced. It can be seen that when Li + The oxygen vacancies in this part are unstable and the voltage will be returned to the electrolyte as they fade. However, the oxygen vacancies in the double-layer film covered with an amorphous layer and the single-layer amorphous film have no obvious changes in fading and coloring.
[0039] A comprehensive analysis of the performance of the WO3 thin film with a lower crystalline layer and an upper amorphous structure prepared in Example 1 above shows that the optical transmittance and cycle stability of the example film are greatly improved compared with the comparative example, and the light modulation range is 62.71%. Moreover, after 600 cycles, it still has good electrochromic and optical properties, and the optical modulation range after cycling is 45.03%.
Claims
1. A method for preparing an amorphous and crystalline WO3 double-layer electrochromic film, characterized in that: The following steps are involved: (1) Take the cut conductive glass ITO and use acetone, anhydrous ethanol and deionized water to ultrasonically clean it in sequence, and use a nitrogen gun to blow away the residual moisture on the surface of the substrate; (2) Based on WO3 target, amorphous WO3 thin film a-WO3 with a thickness of 110nm-120nm was prepared at room temperature by radio frequency magnetron sputtering; (3) Annealing treatment is continued for 1.5h-2.5h at 350°C-450°C in air atmosphere to obtain a crystalline WO3 film c-WO3; (4) Based on the c-WO3 film, the a-WO3 film with a thickness of 140nm-155nm was prepared at room temperature using a magnetron sputtering method based on the WO3 target material to obtain a double-layer film with an upper layer of a-WO3 and a lower layer of c-WO3.
2. The method for preparing an amorphous and crystalline WO3 double-layer electrochromic film according to claim 1, characterized in that: The size of the conductive glass ITO cut in step (1) is 1.0 cm×2.0 cm, and the cleaning time is 10 min to 15 min.
3. The method for preparing an amorphous and crystalline WO3 double-layer electrochromic film according to claim 1, characterized in that: In the step (2), the WO3 target material has a diameter of 50 mm, a thickness of 5 mm and a purity of 99.99%.
4. The method for preparing an amorphous and crystalline WO3 double-layer electrochromic film according to claim 1 or 3, characterized in that: The magnetron sputtering conditions in step (2) are: power of 90W-110W, ratio of argon to oxygen of 100:0-70:30, chamber pressure of 0.8Pa-2.0Pa at room temperature, and sputtering time of 10min-20min.
5. The method for preparing an amorphous and crystalline WO3 double-layer electrochromic film according to claim 4, characterized in that: The magnetron sputtering conditions in step (2) are: sputtering power of 100 W, argon to oxygen ratio of 90:10, chamber pressure maintained at 1.4 Pa at room temperature, and sputtering time of 15 min.
6. The method for preparing an amorphous and crystalline WO3 double-layer electrochromic film according to claim 1, characterized in that: In the step (3), the annealing treatment is continuously performed for 2 hours at 400° C. in an air atmosphere.
7. The method for preparing an amorphous and crystalline WO3 double-layer electrochromic film according to claim 1, characterized in that: In step (4), the WO3 target material has a diameter of 50 mm, a thickness of 5 mm and a purity of 99.99%.
8. The method for preparing an amorphous and crystalline WO3 double-layer electrochromic film according to claim 1 or 7, characterized in that: The magnetron sputtering conditions in step (4) are: power of 90W-110W, ratio of argon to oxygen of 100:0-70:30, pressure in the chamber maintained at 0.8Pa-2.0Pa at room temperature, and sputtering time of 25min-35min.
9. The method for preparing an amorphous and crystalline WO3 double-layer electrochromic film according to claim 8, characterized in that: The magnetron sputtering conditions in step (4) are: sputtering power of 100 W, argon to oxygen ratio of 90:10, chamber pressure maintained at 1.4 Pa at room temperature, and sputtering time of 30 min.
10. An amorphous and crystalline WO3 double-layer electrochromic film prepared by the method according to any one of claims 1 to 9.
Citation Information
Cited By
Porous magnetron sputtering electrochromic film as well as preparation method and application thereof
CN121046800A
